2023
DOI: 10.3390/math11092014
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Supplier Selection and Order Allocation Using an Integrated ROG-Based Type-2 Fuzzy Decision-Making Approach

Abstract: The sustainable Supplier Evaluation and Selection and Order Allocation (SSOA) problem has received significant attention in supply chain management due to its potential to enhance a company’s performance, improve customer satisfaction, and reduce costs. In this study, an integrated methodology is proposed to address the SSOA problem. The methodology combines multiple techniques to handle the uncertainties associated with supplier evaluation, including a new ranking method based on the concept of Radius of Gyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The Q-ROF Positive Ideal Solution (PIS) and Negative Ideal Solution (NIS) values presented in Table 10 were computed utilizing the equations outlined in Equations ( 21)- (25), with the q-value set to 3. The separation measures were calculated using Equations ( 26) and (27). Afterward, proximity values to the ideal solution were established, guiding the determination of rankings for the alternatives.…”
Section: Selection With Q-rof Topsis Methodsmentioning
confidence: 99%
“…The Q-ROF Positive Ideal Solution (PIS) and Negative Ideal Solution (NIS) values presented in Table 10 were computed utilizing the equations outlined in Equations ( 21)- (25), with the q-value set to 3. The separation measures were calculated using Equations ( 26) and (27). Afterward, proximity values to the ideal solution were established, guiding the determination of rankings for the alternatives.…”
Section: Selection With Q-rof Topsis Methodsmentioning
confidence: 99%
“…The outcomes of these applications have shown that MCDM methods can help to identify the most sustainable manufacturing processes and products and support the transition towards a circular economy. Furthermore, applying these methods in the specific context [92] can enhance sustainable decision-making practices.…”
Section: Case Studies: Applications Of Mcdm Methods In Sustainable En...mentioning
confidence: 99%
“…of companies in today's global economy [3,4]. This process significantly influences the company's efficiency, profitability, flexibility, and speed.…”
mentioning
confidence: 99%